CPEB4 knockout mice exhibit normal hippocampus-related synaptic plasticity and memory. - Li-Yun Tsai; Yu-Wei Chang; Pei-Yi Lin; Hsin-Jung Chou; Ta-Jen Liu; Ping-Tao Lee; Wen-Hsuan Huang; Yueh-Liang Tsou; Yi-Shuian Huang (PLoS ONE, 2013)
Regulated RNA translation is critical to provide proteins needed to maintain persistent modification of synaptic strength, which underlies the molecular basis of long-term memory (LTM). Cytoplasmic polyadenylation element-binding proteins (CPEBs) are sequence-specific RNA-binding proteins and regulate translation in various tissues. All four CPEBs in vertebrates are expressed in the brain, including the hippocampal neurons, suggesting their potential roles in translation-dependent plasticity and memory. Although CPEB1 and CPEB3 have been shown to control specific kinds of hippocampus-related LTM, the role of CPEB2 and CPEB4 in learning and memory remains elusive. Thus, we generated CPEB4 knockout (KO) mice and analyzed them using several behavioral tests. No difference was found in the anxiety level, motor coordination, hippocampus-dependent learning and memory between the KO mice and their wild-type (WT) littermates. Electrophysiological recordings of multiple forms of synaptic plasticity in the Schaffer collateral pathway-CA1 neurons also showed normal responses in the KO hippocampal slices. Morphological analyses revealed that the CPEB4-lacking pyramidal neurons possessed slightly elongated dendritic spines. Unlike its related family members, CPEB1 and CPEB3, CPEB4 seems to be dispensable for hippocampus-dependent plasticity, learning and memory.